Manajemen Tenaga Pendidik dan Kependidikan dalam Meningkatkan Mutu Pendidikan di Indonesia: Kajian Literatur - Sri Inayati Ningrum; Musyarapah Musyarapah; Santi Erliana (Educational Journal, 2026)
This study aims to analyze the management of educational and non-educational personnel in the context of improving the quality of education in Indonesia. Using a descriptive qualitative method through literature review and document analysis, the study explores the definitions, roles, functions, and major challenges faced in managing teachers and educational staff. The findings indicate that several significant problems persist, including low levels of professionalism among educators, uneven distribution of qualified teachers, limited access to professional development, weak managerial capacity of school leaders, and insufficient use of educational technology. To address these issues, the study highlights strategic efforts such as increasing teacher qualifications, providing structured training and scholarships, ensuring equitable deployment of personnel, enhancing welfare, and strengthening evaluation and supervision systems. The conclusion emphasizes that effective and sustainable personnel management is essential for building a professional and adaptive educational workforce capable of supporting a quality education system that meets the demands of the times.